Communicable Diseases Intelligence volume 22 issue 11 - October 1998-whole issue - No authors listed, (Communicable Diseases Intelligence, 1998)
Contents Report of the Australian Malaria Register for 1992 and 1993 Editorial comment Trends in malaria in Australia, 1991-1997 VRE; a public comment Emergence and epidemiology of vancomycin-resistant enterococci in Australia Measles Control Campaign update CDI instructions for authors Communicable Diseases Surveillance: Highlights (vaccine preventable diseases, arboviruses, hepatitis A, meningococcal infection, SLTEC infections - HUS and TTP) National Notifiable Diseases Surveillance System tables, 16 September to 13 October 1998 Laboratory Serology and Virology Reporting Scheme tables, 10 September to 7 October 1998 Australian Sentinel Practice Research Network report tables, weeks 36 to 39, 1998 National influenza surveillance 1998 (year to date) HIV and AIDS surveillance, reporting period 1 to 31 May 1998, assessed as at 31 August 1998 Bulletin board Overseas briefs (diarrhoeal diseases, cholera) Correction (HIV and AIDS surveillance, reporting period 1 to 30 April 1998, assessed as at 31 July 1998)